2017
DOI: 10.2147/tcrm.s142828
|View full text |Cite
|
Sign up to set email alerts
|

Serum bone alkaline phosphatase is a useful marker to evaluate lumbar bone mineral density in Japanese postmenopausal osteoporotic women during denosumab treatment

Abstract: A worldwide health concern, osteoporosis (OP), increases the risk of bone fracture and results in morbidity. This study examined whether the representative bone absorption marker serum tartrate-resistant acid phosphatase 5b (TRACP-5b) or bone formation marker bone alkaline phosphatase (BAP) could estimate primary OP status and denosumab efficacy in a real-world setting. We retrospectively enrolled 114 female postmenopausal primary OP patients in Japan. Values and percent changes in TRACP-5b, BAP, lumbar 1–4 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Our study is to date the first to show that higher blood Hcy is associated with elevated alkaline phosphatase, both cross-sectionally and longitudinally. Thus, although the main modifiers of Hcy are B-vitamins, particularly folate and vitamin B-12, liver enzymes are correlates of Hcy that can be modulated with reduced alcohol consumption [55], and alkaline phosphatase in particular is a key mediator in the reported association between Hcy and reduction in bone mineral density associated with osteoporosis among postmenopausal women [56,57]. Thus, Hcy may be merely a marker of certain health outcomes, while liver enzyme elevations can act as the main causal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is to date the first to show that higher blood Hcy is associated with elevated alkaline phosphatase, both cross-sectionally and longitudinally. Thus, although the main modifiers of Hcy are B-vitamins, particularly folate and vitamin B-12, liver enzymes are correlates of Hcy that can be modulated with reduced alcohol consumption [55], and alkaline phosphatase in particular is a key mediator in the reported association between Hcy and reduction in bone mineral density associated with osteoporosis among postmenopausal women [56,57]. Thus, Hcy may be merely a marker of certain health outcomes, while liver enzyme elevations can act as the main causal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of calcium and phosphorus in urine was drastically decreased by the administration of AKBA and estradiol, and a possible explanation for these findings could be the estrogenic effect of AKBA. Higher ALP in serum generally happens in diseases of bone and liver [ 48 ]. An increase in the level of ALP was observed in ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two biochemical markers of bone turnover, bone-specific alkaline phosphatase (BAP) and N-terminal telopeptide (NTX), were associated negatively with bone related traits, such as total tibia vBMD and cortical vBMD, which were consistent with previous results. (26)(27)(28)(29) To investigate associations between clinical outcomes and the metabolites that responded differently between L. reuteri and placebo groups, we calculated the Pearson's correlation coefficients between clinical characteristics and differential metabolites at baseline and 12 months, respectively. We found that 13 and 9 metabolites were correlated (P < 0.05) with total tibia vBMD at baseline and 12 months, respectively (Supplemental…”
Section: Associations Between Metabolic Levels and Clinical Outcomesmentioning
confidence: 99%